Anaplastic myxopapillary ependymoma in an infant: Case report and literature review - Trivedi, Darshan (Intractable Rare Dis Res, 2017)
A 7-month-old boy presented with gastrointestinal disturbance, mild neurologic deficit of the left lower extremity and levo-scoliosis of the thoracic spine. Magnetic resonance imaging demonstrated a large intramedullary lesion involving the thoracic spine, from level T1 to T11. Histologic analysis showed a glial tumor with fibrillary processes arranged in radial pattern around mucoid fibrovascular cores with a high proliferative index (focally up to 80%) and prominent vascular endothelial hyperplasia. These findings were consistent with an anaplastic myxopapillary ependymoma. Subtotal resection was performed via a T3–T10 laminoplasty. A ventricular shunt was placed, and the patient subsequently received chemoradiation therapy. To date, this is the second case of a myxopapillary ependymoma with high-grade anaplastic features and the first case in an infant reported in the literature.